ALİ (EDİRNELİ HÜSEYİN EFENDİ) HAYATI, SANATI, ESERLERİ VE DİVANININ TENKİTLİ METNİ - ARIKOĞLU, İSMAİL (Fırat Üniveristesi, 1999)
[Abstract Not Available]
Ali (Hüseyin Efendi from Edirne) his life, art and works together with a critical context of his
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature